2010
DOI: 10.1088/0967-3334/31/5/004
|View full text |Cite
|
Sign up to set email alerts
|

How to detect and reduce movement artifacts in near-infrared imaging using moving standard deviation and spline interpolation

Abstract: Near-infrared imaging (NIRI) is a neuroimaging technique which enables us to non-invasively measure hemodynamic changes in the human brain. Since the technique is very sensitive, the movement of a subject can cause movement artifacts (MAs), which affect the signal quality and results to a high degree. No general method is yet available to reduce these MAs effectively. The aim was to develop a new MA reduction method. A method based on moving standard deviation and spline interpolationwas developed. It enables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
476
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 542 publications
(477 citation statements)
references
References 35 publications
1
476
0
Order By: Relevance
“…Therefore, application of specially designed signal processing algorithms will further reduce MAs, e.g. (Barker et al 2013, Cooper et al 2012, Izzetoglu et al 2005, Molavi and Dumont 2011, Robertson et al 2010, Sato et al 2006, Scholkmann et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, application of specially designed signal processing algorithms will further reduce MAs, e.g. (Barker et al 2013, Cooper et al 2012, Izzetoglu et al 2005, Molavi and Dumont 2011, Robertson et al 2010, Sato et al 2006, Scholkmann et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unintentionally performed stimulus/task-evoked movements of the head may lead to movement artifacts. These are mostly due to changes in light coupling to the tissue, but part could also be due to genuine changes in CBF/CBV, in the fNIRI signal (Izzetoglu et al, 2005;Kurihara et al, 2003;Özgören et al, 2012;Scholkmann et al, 2010;Takahashi et al, 2012;Tax et al, 2011). That also the saliva secretion rate is accompanied with changes in extracerebral hemodynamics was initially shown by Sato et al (2011) and recently confirmed by Matsumoto et al (2012).…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…, and StO2 signals were removed using the method presented in [8]. Thereby, care was taken to ensure that no artificial new trends were introduced to the signals.…”
Section: Movement Artifacts In [O2hb] [Hhb] [Thb]mentioning
confidence: 99%